Iron-carbon composite material, preparation method thereof and application of iron-carbon composite material to synchronous removal of perfluorinated and polyfluoroalkyl compounds

By anchoring iron metal elements onto the carbon support material in the form of nanoclusters to form iron-carbon composite materials, the problem of easy dissolution of traditional iron-carbon materials is solved, and rapid and efficient removal and efficient adsorption of PFAS are achieved.

CN119386820APending Publication Date: 2025-02-07INST OF SOIL SCI CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411933235.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When dealing with PFAS pollution in water, the adsorption rate is slow and the adsorption capacity is limited. In addition, traditional iron-carbon materials are prone to iron dissolution, resulting in new pollution.

Method used

By anchoring the iron metal elements onto the carbon support material in the form of nanoclusters, the iron-carbon composite material is formed, and the iron dissolution problem is avoided and the adsorption rate and capacity are improved.

Benefits of technology

It realizes rapid and efficient removal of PFAS, avoids new pollution caused by iron dissolution, has a large adsorption capacity, is suitable for recycling, and shows excellent adsorption performance in the treatment of various pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386820A_ABST
    Figure CN119386820A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and particularly relates to an iron-carbon composite material, a preparation method of the iron-carbon composite material and application of the iron-carbon composite material to synchronous removal of perfluoro and polyfluoroalkyl compounds. According to the iron-carbon composite material provided by the invention, the iron metal element is anchored on the carbon carrier material in a nanocluster form, so that the problem of new pollution caused by iron dissolution is avoided, and the iron-carbon composite material is high in adsorption rate, large in adsorption capacity, recyclable and good in long-term stability. According to the invention, the PFAS is captured through hydrophobic interaction and electrostatic attraction by utilizing the coding characteristics, excellent adsorption performance is shown in treatment of various pollutants, rapid, efficient and synchronous removal of the PFAS is realized, and meanwhile, the high utilization rate of the iron-carbon composite material is ensured. As an adsorbent, the iron-carbon composite material provided by the invention is particularly suitable for repairing a perfluorooctanoic acid and / or perfluorooctane sulfonic acid combined polluted water body, the repairing is efficient, the cost is low, the removal condition of pollutants can be accurately judged, and the iron-carbon composite material is suitable for underground water or surface water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to an iron-carbon composite material and a preparation method thereof and application thereof in the simultaneous removal of perfluorinated and polyfluorinated alkyl compounds. Background Art

[0002] Per- and polyfluoroalkyl substances (PFAS) refer to aliphatic organic fluorine compounds in which hydrogen is partially or completely replaced by fluorine in the molecular structure. The carbon atoms on the PFAS carbon chain are all sp3 hybridized, and the CF bond formed has a high bond energy. Therefore, PFAS has high thermal stability and chemical inertness. It is widely used as a surfactant, flame retardant, fluororubber and textile finishing agent in the textile, industrial and equipment fields, and is also often added to personal care products. As typical PFAS, perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) have certain carcinogenicity, neurotoxicity, reproductive toxicity and genotoxicity, can be enriched through the food chain, and pose a threat to human health. Therefore, it is urgent to seek efficient PFAS remediation technology.

[0003] The current technical means used to treat PFAS pollution in water bodies mainly include adsorption, photocatalysis, nanofiltration, advanced reduction and electrolysis. Adsorption is the most commonly used treatment method due to its economy and ease of operation. Carbon-based materials have diverse structures and many excellent properties, making them good adsorbents for treating PFAS, but in practical applications they have disadvantages such as slow adsorption rate and limited adsorption capacity.

[0004] In response to the above problems, researchers found that some PFAS exist in the form of anions in water, and the adsorption mechanism usually involves hydrophobic interactions, electrostatic interactions and hydrogen bonds. Therefore, introducing positively charged, abundant and relatively environmentally friendly Fe into the carbon skeleton may effectively improve the removal efficiency of PFAS by the adsorbent. However, traditional iron-carbon materials are often prone to iron dissolution and other phenomena, generating new pollution, which is limited in practical applications. Summary of the invention

[0005] The purpose of the present invention is to provide an iron-carbon composite material, a preparation method thereof and an application for the simultaneous removal of perfluoro and polyfluoroalkyl compounds. In the iron-carbon composite material provided by the present invention, the iron metal element is anchored on the carbon carrier material in the form of nanoclusters, thereby avoiding the problem of new pollution caused by iron dissolution.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The invention provides an iron-carbon composite material, comprising a carrier material and metal nanoclusters anchored on the carrier material; the metal nanoclusters are iron; and the carrier material is carbon and nitrogen.

[0007] Preferably, the mass ratio of the carrier material to the metal nanoclusters is 1:0.059 to 1:0.098.

[0008] Preferably, the mass ratio of carbon to nitrogen is 15:1 to 25:1.

[0009] The present invention also provides a method for preparing the iron-carbon composite material described in the above scheme, comprising the following steps: A zinc salt, an iron salt and a first organic solvent are mixed to obtain a liquid A; 2-methylimidazole and a second organic solvent are mixed to obtain a liquid B; the liquids A and B are mixed and then aged and calcined in sequence to obtain an iron-carbon composite material.

[0010] Preferably, the mass ratio of the zinc salt to the first organic solvent is 1:20~1:50; the molar ratio of iron in the iron salt to zinc in the zinc salt is 0.1:1~2:1; the concentration of 2-methylimidazole in the B solution is 16.42~82.1 g / L; and the volume ratio of the A solution to the B solution is 1:0.5~1:3.

[0011] Preferably, the aging is carried out under static conditions; the aging time is 10 to 72 hours.

[0012] Preferably, the calcination is carried out in a protective atmosphere; the calcination temperature is 800-1000°C, and the holding time is 1-3 h.

[0013] Preferably, the system is heated before calcination; the heating rate is 2-5 °C / min.

[0014] The present invention also provides the use of the iron-carbon composite material described in the above scheme or the iron-carbon composite material obtained by the preparation method described in the above scheme for simultaneously removing perfluoro and polyfluoroalkyl compounds.

[0015] Preferably, the application comprises the following steps: mixing the iron-carbon composite material and the water body contaminated by perfluoro or polyfluoroalkyl compounds for adsorption; the dosage of the iron-carbon composite material is 0.1-0.5 g / L.

[0016] The present invention provides an iron-carbon composite material. The iron-carbon composite material provided by the present invention anchors metal elements on a carrier material carbon in the form of nanoclusters, and iron exists in the form of carbon-loaded iron, thereby avoiding the problem of new pollution caused by iron dissolution, having a high adsorption rate, a large adsorption capacity, recyclability, and good long-term stability. The present invention utilizes the above-mentioned coding characteristics to capture PFAS through hydrophobic action and electrostatic attraction, exhibits excellent adsorption performance in the treatment of multiple pollutants, realizes rapid, efficient, and synchronous removal of PFAS, and ensures high utilization of the iron-carbon composite material.

[0017] The present invention also provides a method for preparing the iron-carbon composite material described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation and good feasibility.

[0018] The present invention also provides the use of the iron-carbon composite material described in the above scheme or the iron-carbon composite material obtained by the preparation method described in the above scheme for the simultaneous removal of perfluoro and polyfluoroalkyl compounds. The iron-carbon composite material provided by the present invention is used as an adsorbent, which is particularly suitable for the repair of water bodies contaminated by perfluorooctanoic acid and perfluorooctane sulfonic acid. It is easy to operate, has high efficiency in repair, and low cost. It can accurately judge the removal of pollutants, is suitable for groundwater or surface water, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a diagram showing the removal effect of PFOA and PFOS by the iron-carbon composite material of Example 1 of the present invention; Figure 2 The XRD pattern of the iron-carbon composite material of Example 1 of the present invention; Figure 3 This is the SEM spectrum of the iron-carbon composite material of Example 1 of the present invention; Figure 4 This is the TEM spectrum of the iron-carbon composite material of Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The invention provides an iron-carbon composite material, comprising a carrier material and metal nanoclusters anchored on the carrier material; the metal nanoclusters are iron; and the carrier material is carbon and nitrogen.

[0022] The iron-carbon composite material provided by the present invention comprises a carrier material; the carrier material is carbon and nitrogen; the mass ratio of the carbon to nitrogen is preferably 15:1 to 25:1, specifically 15:1, 17:1, 20:1, 22:1 or 25:1.

[0023] The iron-carbon composite material provided by the present invention includes metal nanoclusters; the mass ratio of the carrier material to the metal nanoclusters is preferably 1:0.059 to 1:0.098, and specifically can be 1:0.059, 1:0.065, 1:0.070, 1:0.075, 1:0.080, 1:0.085, 1:0.090, 1:0.095 or 1:0.098. The present invention is more conducive to the rapid removal of PFOA and PFOS composite pollution in water bodies through the above dosage.

[0024] The present invention also provides a method for preparing the iron-carbon composite material described in the above scheme, comprising the following steps: A zinc salt, an iron salt and a first organic solvent are mixed to obtain a liquid A; 2-methylimidazole and a second organic solvent are mixed to obtain a liquid B; the liquids A and B are mixed and then aged and calcined in sequence to obtain an iron-carbon composite material.

[0025] The present invention mixes zinc salt, iron salt and a first organic solvent (referred to as the first mixture) to obtain liquid A. In the present invention, the zinc salt preferably includes one or more of zinc nitrate and zinc nitrate hexahydrate. The present invention adds zinc to form a coordination with an organic ligand 2-methylimidazole to construct a skeleton structure of the material.

[0026] In the present invention, the iron salt is preferably one or more of iron phthalocyanine, iron acetylacetonate and iron nitrate; and the iron phthalocyanine is preferably iron phthalocyanine (II).

[0027] In the present invention, the molar ratio of the iron in the iron salt to the zinc in the zinc salt is 0.1:1 to 2:1, specifically 0.1:1, 0.2:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1. The present invention regulates the pore structure and configuration of the iron-carbon composite material by using the above-mentioned amount of metal salt.

[0028] In the present invention, the first organic solvent is preferably an alcohol; the alcohol is preferably a C1-C8 alcohol; the C1-C8 alcohol is preferably methanol.

[0029] In the present invention, the mass ratio of the zinc salt to the first organic solvent is preferably 1:20-1:50, specifically 1:20, 1:30, 1:40 or 1:50.

[0030] In the present invention, the first mixing is preferably stirring mixing.

[0031] In the present invention, 2-methylimidazole and a second organic solvent are mixed (referred to as the second mixture) to obtain liquid B. In the present invention, the second organic solvent is preferably an alcohol; the alcohol is preferably a C1-C8 alcohol; and the C1-C8 alcohol is preferably methanol.

[0032] In the present invention, the concentration of 2-methylimidazole in the B solution is preferably 16.42-82.1 g / L, specifically 16.42 g / L, 25.3 g / L, 34.5 g / L, 43.6 g / L, 54.73 g / L, 62.7 g / L, 71.3 g / L or 82.1 g / L. In the present invention, 2-methylimidazole is coordinated with zinc ions to construct the skeleton structure of the material.

[0033] In the present invention, the second mixing is preferably stirring mixing.

[0034] After obtaining liquid A and liquid B, the present invention mixes the liquid A and liquid B (referred to as the third mixing), and then sequentially ages and calcines them to obtain an iron-carbon composite material.

[0035] In the present invention, the volume ratio of liquid A to liquid B is preferably 1:0.5-1:3, specifically 1:0.5, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.

[0036] In the present invention, the third mixing is preferably stirring mixing; the rotation speed of the third mixing is preferably 50-500 rpm, specifically 50 rpm, 100 rpm, 300 rpm or 500 rpm, and the mixing time is preferably 2-24 h, specifically 2 h, 6 h, 10 h, 15 h, 20 h or 24 h.

[0037] In the present invention, the aging is preferably carried out under static conditions; the aging time is preferably 10 to 72 h, specifically 10 h, 15 h, 24 h, 36 h, 48 h, 60 h or 72 h.

[0038] The present invention helps orderly growth of crystals through aging, reduces structural defects and improves product quality and performance.

[0039] In the present invention, the aging process preferably further comprises washing and drying the aged product in sequence.

[0040] In the present invention, the washing is preferably alcohol washing; the alcohol used in the alcohol washing is preferably anhydrous ethanol.

[0041] In the present invention, the drying is preferably oven drying; the drying temperature is preferably 60-120°C, specifically 60°C, 70°C, 80°C, 100°C or 120°C; the heat preservation and drying time is preferably 12-18 h, specifically 12 h, 14 h, 16 h or 18 h; the drying equipment is preferably a vacuum drying oven.

[0042] In the present invention, the calcination is preferably carried out in a protective atmosphere; the protective atmosphere is preferably nitrogen; the calcination temperature is preferably 800-1000°C, specifically 850°C, 900°C or 950°C, the holding time is preferably 1-3h, specifically 2h; the calcination equipment is preferably a tubular furnace. The present invention further carbonizes the material through calcination, and volatilizes the zinc added in the preparation process, leaving only the metallic iron component.

[0043] In the present invention, the system is preferably heated before calcination; the heating rate is preferably 2-5°C / min, specifically 3°C / min or 5°C / min. The present invention adopts the above heating rate so that the grains have sufficient time to grow and form a more uniform and dense microstructure.

[0044] In the present invention, the calcination preferably further comprises cooling the calcined product.

[0045] The present invention also provides the use of the iron-carbon composite material described in the above scheme or the iron-carbon composite material obtained by the preparation method described in the above scheme for simultaneously removing perfluoro and polyfluoroalkyl compounds.

[0046] In the present invention, the use of the iron-carbon composite material for the simultaneous removal of perfluoro and polyfluoroalkyl compounds preferably comprises the following steps: The iron-carbon composite material and the water body contaminated by perfluoroalkyl or polyfluoroalkyl compounds are mixed (referred to as the fourth mixing) for adsorption.

[0047] In the present invention, the concentration of PFOA in the perfluoro or polyfluoroalkyl compound-contaminated water is preferably 0.001-10 mg / L, and the concentration of PFOS is preferably 0.001-10 mg / L.

[0048] In the present invention, the dosage of the iron-carbon composite material is preferably 0.1-0.5 g / L, specifically 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L or 0.5 g / L.

[0049] In the present invention, the fourth mixing is preferably oscillating mixing; the temperature of the fourth mixing is preferably 15-55°C, specifically 15°C, 25°C, 35°C, 45°C or 55°C, and the mixing time is preferably 2-360 min, specifically 2 min, 20 min, 60 min, 120 min, 180 min, 240 min, 300 min or 360 min. The present invention promotes the adsorption of the iron-carbon composite material by oscillation.

[0050] In the present invention, the adsorption is preferably performed under light-shielding conditions.

[0051] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0052] Example 1 Solution A was prepared by dissolving 2.975 g of zinc nitrate hexahydrate and 0.568 g of iron (II) phthalocyanine in 150 mL of methanol; Prepare Solution B by dissolving 8.21 g of 2-methylimidazole in 150 mL of methanol; The liquid A and the liquid B were quickly mixed and stirred for 2 h, aged for 24 h, washed with anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain a blue solid; The obtained blue solid was placed in a tube furnace and heated under N 2 The mixture was heated to 900 °C at a heating rate of 5 °C / min in an atmosphere and calcined for 2 h. Then, the mixture was cooled to obtain an iron-carbon composite material.

[0053] The iron-carbon composite material prepared in this example was subjected to adsorption tests, including the removal of PFOA alone, the removal of PFOS alone, and the simultaneous removal of PFOA and PFOS combined pollution, and the efficiencies of the three were compared.

[0054] (A) PFOA removal system alone (1) In a 22 mL borosilicate glass bottle lined with a screw cap and a silicone pad, add 20 mL of water with a PFOA concentration of 1 mg / L and 4 mg of the iron-carbon composite material; (2) After sealing, the borosilicate glass bottle was shielded from light with aluminum foil and then placed in a constant temperature oscillator with a rotation speed of 150 rpm, a temperature set to 25 °C, and an oscillation time of 6 h.

[0055] (B) PFOS removal system alone (1) In a 22 mL borosilicate glass bottle lined with a screw cap and a silicone pad, add 20 mL of water with a PFOS concentration of 1 mg / L and 4 mg of the iron-carbon composite material; (2) After sealing, the borosilicate glass bottle was shielded from light with aluminum foil and then placed in a constant temperature oscillator with a rotation speed of 150 rpm, a temperature set to 25 °C, and an oscillation time of 6 h.

[0056] (C) PFOA-PFOS composite pollution system (1) In a 22 mL borosilicate glass bottle lined with a screw cap and a silicone pad, add 20 mL of water with a PFOA concentration of 1 mg / L and a PFOS concentration of 1 mg / L, and 4 mg of the iron-carbon composite material; (2) After sealing, the borosilicate glass bottle was shielded from light with aluminum foil and then placed in a constant temperature oscillator with a speed of 150 rpm, a temperature set to 25 °C, and an oscillation time of 6 h. The results are shown in Tables 1 and Figure 1 shown.

[0057] Table 1 Adsorption test results of Example 1

[0058] According to Table 1 and Figure 1 It can be seen that the removal efficiency of the iron-carbon composite material for PFOA and PFOS alone is 99.61% and 99.77% respectively; moreover, the iron-carbon composite material can achieve rapid, efficient and synchronous removal of PFOA and PFOS combined pollution in water bodies, and the removal rate of both PFOA and PFOS can reach 95%, which is comparable to the removal effect of the PFOA system alone and the PFOS system alone.

[0059] Example 2 This example uses the iron-carbon composite material of Example 1 to conduct an adsorption test to detect the effect of pollutant concentration on the removal of PFOA and PFOS by the iron-carbon composite material.

[0060] (1) In a 22 mL borosilicate glass bottle lined with a screw cap and a silica pad, 20 mL of water containing different concentrations (0.1, 1, 2, 5, 10, and 25 mg / L) of PFOA and PFOS and 4 mg of the iron-carbon composite were added; (2) After sealing, the borosilicate glass bottle was shielded from light with aluminum foil and then placed in a constant temperature oscillator with a rotation speed of 150 rpm, a temperature set to 25 °C, and an oscillation time of 2 h. The results are shown in Table 2.

[0061] Table 2 Adsorption test results of Example 2

[0062] It can be seen from Table 2 that the iron-carbon composite material of the present invention is affected by the concentration of PFOA and PFOS, and exhibits different removal effects: when the concentration of PFOA and PFOS in the water increases, the pollutant removal rate decreases accordingly; when the pollutant concentration is lower than 5 mg / L, PFOA and PFOS in the water are almost completely removed; when the pollutant concentration is 10 mg / L, the removal rate of PFOS in the water is still higher than 90%, and the removal rate of PFOA drops to 53.64%; when the pollutant concentration is 25 mg / L, the removal rate of PFOS in the water also decreases, but is still higher than the removal rate of PFOA.

[0063] Test Case The iron-carbon composite material prepared in Example 1 was subjected to XRD, SEM and TEM tests, and the results were as follows: Figure 2 , Figure 3 , Figure 4 As shown. Figures 2~4 It can be seen that the iron material prepared in the present invention exists in the form of metal clusters with a diameter of ~100 nm.

[0064] The Fe content of the supernatant of Example 1 was detected by inductively coupled plasma-optical emission spectroscopy (ICP-OES). The detection method was based on the "Determination of 32 Elements in Water Quality by Inductively Coupled Plasma Optical Emission Spectrometry (HJ 776-2015)". The results are shown in Table 3.

[0065] Table 3 Test results of Fe dissolution test

[0066] It can be seen from Table 3 that the material was relatively stable during the adsorption process and no iron dissolution was detected.

[0067] It can be seen from the above embodiments that the iron-carbon composite material provided by the present invention has a high adsorption rate and a large adsorption capacity, thereby achieving rapid and efficient simultaneous removal of PFAS.

[0068] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An iron-carbon composite material, characterized in that: The invention comprises a carrier material and metal nanoclusters anchored on the carrier material; the metal nanoclusters are iron; and the carrier material is carbon and nitrogen.

2. The iron-carbon composite material according to claim 1, characterized in that: The mass ratio of the carrier material to the metal nanoclusters is 1:0.059-1:0.

098.

3. The iron-carbon composite material according to claim 1 or 2, characterized in that: The mass ratio of carbon to nitrogen is 15:1 to 25:

1.

4. The method for preparing the iron-carbon composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing zinc salt, iron salt and a first organic solvent to obtain liquid A; Mixing 2-methylimidazole and a second organic solvent to obtain solution B; The A solution and the B solution are mixed and then aged and calcined in sequence to obtain an iron-carbon composite material.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the zinc salt to the first organic solvent is 1:20 to 1:50; The molar ratio of iron in the iron salt to zinc in the zinc salt is 0.1:1 to 2:1; The concentration of 2-methylimidazole in the B solution is 16.42-82.1 g / L; The volume ratio of liquid A to liquid B is 1:0.5 to 1:

3.

6. The preparation method according to claim 4 or 5, characterized in that: The aging is carried out under static conditions; the aging time is 10 to 72 hours.

7. The preparation method according to claim 4, characterized in that: The calcination is carried out in a protective atmosphere; the calcination temperature is 800-1000°C, and the holding time is 1-3 hours.

8. The preparation method according to claim 4 or 7, characterized in that: The system is heated before the calcination; the heating rate is 2-5 °C / min.

9. Use of the iron-carbon composite material according to any one of claims 1 to 3 or the iron-carbon composite material obtained by the preparation method according to any one of claims 4 to 8 in the simultaneous removal of perfluoro and polyfluoroalkyl compounds.

10. The use according to claim 9, characterized in that: The method comprises the following steps: mixing an iron-carbon composite material and a water body polluted by perfluoro or polyfluoroalkyl compounds for adsorption; and the dosage of the iron-carbon composite material is 0.1-0.5 g / L.

Citation Information

Cited By

  • Strengthening-like coagulation water treatment technology based on in-situ generation of PCPs

    CN120247209A

  • A kind of enhanced coagulation water treatment method based on in-situ PCP generation

    CN120247209B